Use of Moodle in Georgian Higher Education: Students’ Perspective (British Journal of Multidisciplinary and Advanced Studies, 2025)
Nowadays, the educational discourse is closely tied to the concept of technological advancement that the 21st century is commonly associated with. Technological advancements have transformed education through the integration of digital learning platforms. Moodle, a widely adopted Learning Management System (LMS), is available across higher educational institutions in Georgia, including Ivane Javakhishvili Tbilisi State University (TSU). Despite its institutional availability, integration of Moodle within the English Philology program remains limited. The paper examines the perceptions and use of Moodle by TSU undergraduate students in English for Specific Purposes (ESP) courses. The study employed a mixed-methods approach, using quantitative and qualitative research methods. The data were collected via a survey questionnaire designed in Google Form and circulated online. A total of 40 purposively selected students (third- and fourth-year) filled in the questionnaire.Following a detailed analysis of the survey, findings reveal that Moodle is primarily used for assessment-related activities (quizzes, homework submission) and accessing course materials, with limited engagement in collaborative or interactive tools such as forums, workshops, and feedback. Usage frequency is moderate, suggesting a supplementary rather than central role in learning. Low awareness of plagiarism detection tools (Turnitin) indicate missed opportunities for enhancing academic integrity and student engagement. Additionally, the paper offers a few recommendations.